Ultra-weak photon emission as a non-invasive tool for monitoring of oxidative processes in the epidermal cells of human skin: comparative study on the dorsal and the palm side of the hand - Rastogi, Anshu; Pospísil, Pavel (Skin research and technology, 2010)
BACKGROUND/PURPOSE: All living organisms emit spontaneous ultra-weak photon emission as a result of cellular metabolic processes. Exposure of living organisms to exogenous factors results in oxidative processes and enhancement in ultra-weak photon emission. Here, hydrogen peroxide (H(2)O(2)), as a strongly oxidizing molecule, was used to induce oxidative processes and enhance ultra-weak photon emission in human hand skin. The presented work intends to compare both spontaneous and peroxide-induced ultra-weak photon emission from the epidermal cells on the dorsal and the palm side of the hand. METHODS: A highly sensitive photomultiplier tube and a charge-coupled device camera were used to detect ultra-weak photon emission from human hand skin. RESULTS: Spontaneous ultra-weak photon emission from the epidermal cells on the dorsal side of the hand was 4 counts/s. Topical application of 500 mM H(2)O(2) to the dorsal side of the hand caused enhancement in ultra-weak photon emission to 40 counts/s. Interestingly, both spontaneous and peroxide-induced ultra-weak photon emission from the epidermal cells on the palm side of the hand were observed to increase twice their values, i.e. 8 and 80 counts/s, respectively. Similarly, the two-dimensional image of ultra-weak photon emission observed after topical application of H(2)O(2) to human skin reveals that photon emission from the palm side exceeds the photon emission from the dorsal side of the hand. CONCLUSION: The results presented indicate that the ultra-weak photon emission originating from the epidermal cells on the dorsal and the palm side of the hand is related to the histological structure of the human hand skin. Ultra-weak photon emission is shown as a non-destructive technique for monitoring of oxidative processes in the epidermal cells of the human hand skin and as a diagnostic tool for skin diseases.
Keywords: Oxidative Stress; oxidační stres; Humans; fyziologie kůže; oxidace-redukce; Radiometry; oxidancia; lidé; radiometrie; Epidermis; Skin Physiological Phenomena; peroxid vodíku; Photons; Oxidants; Oxidation-Reduction; ruka; fotony; Hydrogen Peroxide; epidermis; Hand